Modified transnasal endoscopic medial maxillectomy with inferior turbinate flap for dentigerous cyst - Retno Sulistyo Wardani; Michael Lekatompessy; Brent Anthony Senior (Oto Rhino Laryngologica Indonesiana, 2015)
Background: Dentigerous cyst is one of the most frequent types of odontogenic cyst that usually involving an impacted, supernumerary or ectopically erupted tooth. One of the non-dental sites for ectopiceruption is the maxillary sinus. The traditional approach under such circumstances is a Caldwell-Luc maxillotomy, but this type of procedure may result in significant long-term complications. Endoscopic transnasal medial maxillectomy (ETMM) has several advantages, such as good il lumination, as wellas clear and magnified visualization. The new modified endoscopic transnasal medial maxillectomy(METMM) can provide good visualization and more functional result by preserving the nasolacrimalduct and the inferior turbinate. Purpose: We present this case to introduce the METMM technique forextirpation of any tumor in the maxillary sinus. Case: One case of dentigerous cyst with an ectopicleft maxillary 3 molar tooth in a 27 year old woman who presented with sinusitis. Management:Surgery with a METMM technique to enucleate the cyst, combined with functional endoscopic sinussurgery (FESS) for the sinusitis. The patient then evaluated subjectively for epiphora and objectivelywith nasoendoscopic examination. Conclusion: In this case, METMM was effective in accessing themaxillary sinus allowing for tumor extirpation, while preserving the function of the inferior tubinate andnasolacrimal duct. Keywords : Dentigerous cyst, maxillary ectopic tooth eruption, transnasal medial maxillectomy ABSTRAKLatar belakang: Kista dentigerous merupakan salah satu jenis kista otontogenik yang paling sering ditemukan, biasanya berhubungan dengan gigi impaksi, supernumeri atau gigi yang tumbuhektopik. Salah satu tempat erupsi ektopik adalah sinus maksilaris. Pendekatan tradisional dalamkeadaan ini adalah operasi Caldwell-Luc, tetapi teknik operasi ini dapat mengakibatkan komplikasijangka panjang. Maksilektomi medial transnasal dengan endoskopi (MMTE) memiliki beberapakeunggulan, seperti visualisasi yang jelas dan diperbesar. Teknik maksilektomi medial transnasaldengan endoskopi yang dimodifikasi (MMTEM) dapat memberikan visualisasi yang baik dan hasillebih fungsional dengan mempertahankan duktus nasolakrimal dan konka inferior. Tujuan: makalahini diajukan untuk memperkenalkan teknik MMTEM untuk ekstrirpasi massa yang berada di dalamsinus maksila, karena teknik ini memberikan hasil yang lebih fungsional. Kasus: melaporkan satu kasuskista dentigerous dengan gigi molar 3 yang erupsi ektopik pada sinus maksila kiri pada wanita 27tahun. Penatalaksanaan: kasus ini ditatalaksana dengan teknik MMTEM untuk mengenukleasi kistadan BSEF untuk sinusitis. Pasien kemudian dievaluasi secara subjektif dengan anamnesis mengenaiadanya epifora dan objektif dengan pemeriksaan nasoendoskopi. Kesimpulan: MMTEM terbukti efektifuntuk ekstirpasi tumor yang berada di dalam sinus maksila, dan teknik ini juga memberikan hasil yanglebih fungsional dengan dipertahankannya konka inferior dan duktus nasolakrimal. Kata kunci : Kista dentigerous, erupsi gigi ektopik di maksila, transnasal maksilektomi medial